Vertical Ge photodetector base on InP taper waveguide - Amiri, I.S. (Elsevier B.V., 2018)
In this work, simulation is conducted to investigate Ge photodetectors monolithically integrated on Si chip. The performance of vertical Germanium photodetector with FDTD Solutions (optical simulation) and electrical simulation has been studied. Selective heteroepitaxy of Ge is functioned in the monolithic integration of Ge photodetectors. The potential of CMOS-compatible monolithic integration of Ge as photodetector is investigated and the performance optimization is presented. Additionally, the investigation is extended to electrical part, particularly in the conversion efficiency as well as operation under low supplied voltage condition. Â© 2018 The Authors